The role of type I interferon signaling in myeloid anti-tumor immunity - Meyer, Sofie Patrizia; Bauer, Rebekka; Brüne, Bernhard; Schmid, Tobias (Frontiers in Immunology, 2025)
Tumors often arise in chronically inflamed, and thus immunologically highly active niches. While immune cells are able to recognize and remove transformed cells, tumors eventually escape the control of the immune system by shaping their immediate microenvironment. In this context, macrophages are of major importance, as they initially exert anti-tumor functions before they adopt a tumor-associated phenotype that instead inhibits anti-tumor immune responses and even allows for sustaining a smoldering inflammatory, growth promoting tumor microenvironment (TME). Type I interferons (IFNs) are well established modulators of inflammatory reactions. While they have been shown to directly inhibit tumor growth, there is accumulating evidence that they also play an important role in altering immune cell functions within the TME. In the present review, we focus on the impact of type I IFNs on anti-tumor responses, driven by monocytes and macrophages. Specifically, we will provide an overview of tumor-intrinsic factors, which impinge on IFN-stimulated gene (ISG) expression, like the presence of nucleic acids, metabolites, or hypoxia. We will further summarize the current understanding of the consequences of altered IFN responses on macrophage phenotypes, i.e., differentiation, polarization, and functions. For the latter, we will focus on macrophage-mediated tumor cell killing and phagocytosis, as well as on how macrophages affect their environment by secreting cytokines and directly interacting with immune cells. Finally, we will discuss how type I IFN responses in macrophages might affect and should be considered for current and future tumor therapies.